Food provisioning in Magellanic penguins as inferred from stable isotope ratios. (15th February 2018) - Ciancio, Javier E.; Yorio, Pablo; Wilson, Rory; Frere, Esteban
Abstract : Rationale: Food provisioning is considered one of the main traits affecting offspring fitness. Differences in food provisioning between sexes, particularly in dimorphic species, could affect the amount and type of food provided, due to differences in the amount of food carried to the nest as a result of differential resources exploitation. Quantitative evidence for sexual differences in food provisioning by parents in penguins is scarce. The Magellanic penguin is moderately sexually dimorphic and breeds along a broad latitudinal range, with birds north and south of this range being essentially dietary specialists while those at intermediate latitudes consume a more diverse diet. Methods: We used stable isotope analysis of carbon and nitrogen by isotope ratio mass spectrometry to examine if there was a differential parental contribution to chicks in ten Magellanic penguin colonies throughout its latitudinal breeding distribution. We used the heuristic Euclidean isotopic distance (ED) and individual isotope distances between the chicks and their parents as a proxy for diet similarity (the smaller the distance, the more similar the diet). Results: The analysis showed that chicks tended to have a more similar diet to that of their male parent and that this pattern was more evident at colonies and in seasons where penguins had a more diverse diet, which could be explained by differences in diet between parents. Distance in δ 15 N values, but not in δ 13 C values, differed between both sexes and their chicks in all the pairs sampled, suggesting that δ 15 N values drive the differences found in ED between chicks and their parents. Conclusions: We have developed an approach that provides the first assessment of the extent of differential food provisioning between male and female Magellanic penguins. Results suggest chicks have a diet more similar to that of their male parent, probably related to the higher trophic level of male penguin prey.